Assessment of grating-based X-ray phase-contrast CT for differentiation of invasive ductal carcinoma and ductal carcinoma in situ in an experimental ex vivo set-up - Sztrokay, Aniko; Herzen, Julia; Auweter, Sigrid D.; Liebhardt, Susanne; Mayr, Doris; Willner, Marian; Hahn, Dieter; Zanette, Irene; Weitkamp, Timm; Hellerhoff, Karin; Pfeiffer, Franz; Reiser, Maximilian F.; et al. (European Radiology, 2013)
Objective: Limited contrast between healthy and tumour tissue is a limiting factor in mammography and CT of the breast. Phase-contrast computed tomography (PC-CT) provides improved soft-tissue contrast compared with absorption-based techniques. In this study, we assessed the technical feasibility of grating-based PC-CT imaging of the breast for characterisation of ductal carcinoma in situ (DCIS). Methods: Grating-based PC-CT was performed on one breast specimen containing an invasive ductal carcinoma and DCIS using monochromatic radiation of 23 keV. Phase-contrast and absorption-based images were compared qualitatively and quantitatively with histopathology in a blinded fashion. Results: Grating-based PC-CT showed improved differentiation of soft-tissue components. Circular structures of high phase-shift contrast corresponding to the walls of the dilated ductuli of the DCIS were visualised with a contrast-to-noise ratio (CNR) of 9.6 using PC-CT but were not detectable on absorption-based images (CNR = 0.27). The high phase-shift structures of the dilated ductuli were identifiable in the PC-CT volume data set al.lowing for 3D characterisation of DCIS. Conclusions: Our results indicate that unlike conventional CT, grating-based PC-CT may allow the differentiation between invasive carcinoma and intraductal carcinoma and healthy breast tissue and provide 3D visualisation of DCIS. Key Points: • Phase-contrast computed tomography (CT) yields improved soft-tissue contrast. • The method can resolve the fine structure of a breast tumour. • Invasive and intraductal carcinoma can be differentiated. • Differentiation is possible by visual inspection and quantification. • The method could improve early breast cancer diagnosis. © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed tomography; Ductal carcinoma in situ (DCIS); Invasive ductal carcinoma; Synchrotron radiation; X-ray phase-contrast imaging